2009
DOI: 10.1007/s00405-009-1075-8
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomised, placebo-controlled trial of postoperative oral steroid in allergic fungal sinusitis

Abstract: The aim of this study is to determine the effectiveness of postoperative oral steroid in controlling disease in patients with allergic fungal sinusitis (AFS). The study design includes prospective, randomised, double blind,placebo-controlled trial using oral prednisolone.Twenty-four patients diagnosed with AFS underwent sinus surgery (endoscopic sinus surgery with or without open surgery) to completely excise disease. Patients were randomised to receive either oral steroid (n = 12) or placebo(n = 12) soon afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 11 publications
0
55
0
4
Order By: Relevance
“…One group (n = 12) was treated with oral itraconazole (200 mg/day for 12 weeks) and the other group (n = 12) had oral itraconazole plus oral corticosteroids (50 mg prednisone × 6 weeks and then tapered off over 6 additional weeks. Rupa et al 1106 found that although partial relief of initial sinus symptoms was reported in all 12 patients randomized to 12 weeks of oral itraconazole alone, the nasal endoscopic evaluation revealed that only 1 of the 12 patients had no evidence of disease. This finding contrasted with 8 of the 12 patients having no evidence of disease if oral corticosteroids were added to the oral itraconazole.…”
Section: Antifungal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…One group (n = 12) was treated with oral itraconazole (200 mg/day for 12 weeks) and the other group (n = 12) had oral itraconazole plus oral corticosteroids (50 mg prednisone × 6 weeks and then tapered off over 6 additional weeks. Rupa et al 1106 found that although partial relief of initial sinus symptoms was reported in all 12 patients randomized to 12 weeks of oral itraconazole alone, the nasal endoscopic evaluation revealed that only 1 of the 12 patients had no evidence of disease. This finding contrasted with 8 of the 12 patients having no evidence of disease if oral corticosteroids were added to the oral itraconazole.…”
Section: Antifungal Therapymentioning
confidence: 99%
“…Although uncommon, oral corticosteroids are associated with side effects such as Cushing's disease, blood sugar dyscrasias, gastrointestinal tract ulcer, and avascular necrosis. 1106 Topical corticosteroid use is also related with mild adverse effects, such as nasal dryness, bleeding, burning sense, and throat irritation. 1153 In conclusion, topical corticosteroid can be used as preoperative treatment for better surgical field.…”
Section: Xc1 Crssnp: Preoperative Corticosteroidsmentioning
confidence: 99%
“…Está comprobado que el uso de esteroides sistémicos disminuye la tasa de recurrencia. 8 Se desarrolló interés creciente por el manejo de estos pacientes con antifúngico sistémico como itraconazol, con base en el beneficio que reportaba para pacientes con ABPA; 9 sin embargo, su eficacia en RAF no ha sido establecida y actualmente no se recomienda su uso. 10 Por otro lado, la inmunoterapia se ha convertido de forma reciente en una herramienta terapéutica valiosa en estos pacientes, segura y efectiva, con la capacidad de disminuir las dosis de esteroide tópico sistémico y las tasas de re-intervención.…”
Section: Discussionunclassified
“…Such mucosal changes, if unchecked, can lead to similar pre-operative circumstances requiring surgical intervention. Post-operative oral steroid therapy is well proven to improve symptoms and prevent early recurrences [18] and augments topical corticosteroids. The role of topical antifungals, however, needs to be evaluated to prevent recurrences.…”
Section: Discussionmentioning
confidence: 99%